Intercropping of Faba Bean with Wheat under Different Nitrogen Levels Reduces Faba Bean Rust and Consequent Yield Loss - Luo, Chaosheng; Lv, Jiaxing; Guo, Zengpeng; Dong, Yan (Plant disease, 2022)
While intercropping can help control faba bean rust, the ability of intercropping to reduce this disease under different levels of nitrogen fertilization and its contribution to increasing yield is not clear. In this study, two planting patterns of faba bean monocropping and wheat/faba bean intercropping, together with two treatments for disease control (DC) and non-control (NC), and four nitrogen application levels [N0 (0 kg/ha), N1 (45 kg/ha), N2 (90 kg/ha), and N3 (135 kg/ha)] were tested for two years in a continuous field experiment. The results revealed that nitrogen application increased the area under the progress curve (AUDPC) of faba bean rust from 41.9% to 47.3%, with the N3 treatment resulting in the largest increase. Nitrogen application decreased the relative control efficacy (RCE) of intercropping on faba bean rust. Compared with monocropping, N0 to N3 with intercropping significantly reduced AUDPC by 33.1% for the first year and 28.7% for the second year (P<0.05). Nitrogen application aggravated the faba beans grain yield loss, while the loss of yield components increased in the first year and then declined as the nitrogen application increased, and the yield losses of monocropping were higher than those of intercropping. The N1 and N2 application levels significantly increased the total effect (TE) of intercropping yield advantage by 34.3% and 32.9% in the two years, respectively. During the two years, the overall partial land equivalent ratio (pLER) of faba bean was greater than 0.33. The average disease control effect (DCE)/TE of intercropping was 56.1% and 49.3% for the two years, respectively, indicating that intercropping increased yields and that the contribution of the DCE was close to or higher than that of the other intercropping effects. A regression analysis of the grain yield loss and the AUDPC showed that reducing the nitrogen fertilizer input (N1) could effectively reduce the yield loss caused by rust and enhance the yield. Intercropping of faba bean combined with a suitable nitrogen application (45 kg/ha) is the best treatment to maximize yield by fully utilizing intercropping for managing faba bean rust.